2013
DOI: 10.1038/pcan.2013.49
|View full text |Cite
|
Sign up to set email alerts
|

A genomic classifier predicting metastatic disease progression in men with biochemical recurrence after prostatectomy

Abstract: BACKGROUND Due to their varied outcomes, men with biochemical recurrence (BCR) following radical prostatectomy (RP) present a management dilemma. Here, we evaluate Decipher, a genomic classifier (GC), for its ability to predict metastasis following BCR. METHODS The study population included 85 clinically high-risk patients who developed BCR after RP. Time-dependent receiver operating characteristic (ROC) curves, weighted Cox proportional hazard models and decision curves were used to compare GC scores to Gle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(74 citation statements)
references
References 31 publications
3
69
1
1
Order By: Relevance
“…The prognostic accuracy was highest when the genomic classifier and clinical models (CAPRA-S) were combined [61]. In another study, including 85 highrisk RP patients, the 22-gene panel was the only variable associated with metastatic progression in a multivariable model and had a favorable net benefit compared with clinical models (CAPRA-S and Stephenson postoperative nomogram) [68,74] in decision-curve analysis [71,72]. The test also improved prediction of BCR and metastatic progression risk in a cohort of 139 men undergoing EBRT after RP [73].…”
Section: External Validation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic accuracy was highest when the genomic classifier and clinical models (CAPRA-S) were combined [61]. In another study, including 85 highrisk RP patients, the 22-gene panel was the only variable associated with metastatic progression in a multivariable model and had a favorable net benefit compared with clinical models (CAPRA-S and Stephenson postoperative nomogram) [68,74] in decision-curve analysis [71,72]. The test also improved prediction of BCR and metastatic progression risk in a cohort of 139 men undergoing EBRT after RP [73].…”
Section: External Validation Studiesmentioning
confidence: 99%
“…This panel has also been externally validated in multiple cohorts and is commercially available as the Decipher genetic test (GenomeDX Biosciences, Vancouver, BC, Canada). Four studies reported the utilization of this gene panel to predict BCR, metastatic progression, or DSS after RP plus or minus EBRT [61,[71][72][73]. The prognostic accuracy was highest when the genomic classifier and clinical models (CAPRA-S) were combined [61].…”
Section: External Validation Studiesmentioning
confidence: 99%
“…The GC was then validated on an independent cohort (n=186), outperforming clinical variables and other gene signatures [52]. The GC was clinically validated in two studies on 1095 patients who were clinically high-risk and developed BCR after RP [53,54]. Decipher could independently forecast which patients developed metastasis.…”
Section: Decipher (Genomedx)mentioning
confidence: 99%
“…Prognostic outlier score was defined as the number of prognostic outlier genes with outlier status. Scores were also generated using existing prognostic instruments Decipher, CAPRA-S, and cell-cycle progression (CCP) signature (18,(25)(26)(27)(28). As the CCP signature was ported to our microarray platform, we will refer to the microarray…”
Section: Clinical Validation and Comparison With Published Prognosticmentioning
confidence: 99%